1996
DOI: 10.1007/bf02599584
|View full text |Cite
|
Sign up to set email alerts
|

The effect of an educational intervention on the perceived risk of breast cancer

Abstract: Women often substantially overestimate their chances of getting breast cancer. Educational intervention by a physician, including explanation of an individual's calculated risk, can reduce this error. The effect of education appears to persist at least for several months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
3

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 19 publications
4
51
3
Order By: Relevance
“…For instance, many studies have assessed risk perception to test models that posit an association between risk perception and health behavior (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Other research assesses risk perception to detect errors and biases in risk judgments (15)(16)(17)(18), to assess the association between risk judgments and emotion (19)(20)(21)(22)(23)(24)(25), and to increase the accuracy of people's risk perceptions (11,(26)(27)(28). In sum, several important and large bodies of research depend on obtaining accurate assessments of people's risk perception.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, many studies have assessed risk perception to test models that posit an association between risk perception and health behavior (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Other research assesses risk perception to detect errors and biases in risk judgments (15)(16)(17)(18), to assess the association between risk judgments and emotion (19)(20)(21)(22)(23)(24)(25), and to increase the accuracy of people's risk perceptions (11,(26)(27)(28). In sum, several important and large bodies of research depend on obtaining accurate assessments of people's risk perception.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the percentage of women who overestimated their risk after counselling has ranged from 14% to 89% (Evans et al, 1994;Lerman et al, 1995;Lloyd et al, 1996;Watson et al, 1999). Such over-estimation is associated with high levels of anxiety, and unless corrected, may lead to poorly informed decisions regarding breast cancer screening (Lerman et al, 1993;Alexander et al, 1996;Kash, 1996). Thus it is important to identify strategies which will optimise understanding and psychological adjustment, and these strategies are likely to vary according to the presenting characteristics of the women.…”
mentioning
confidence: 99%
“…Interestingly, women from families with multiple breast and ovarian cancer cases commonly overestimate their cancer risks [15]. For example, for patients participating in chemoprevention trials, the mean lifetime calculated risk using the Gail model was 15%; however, the median risk perceived by patients was 50% [16]. A survey carried out in the USA found that although 75% of Americans were aware of Angelina Jolie's double mastectomy, fewer than 10% of respondents had the information necessary to accurately interpret her risk of developing cancer relative to a woman unaffected by the BRCA gene mutation [17].…”
Section: The Individual Decision-making Processmentioning
confidence: 99%